Transformations des représentations corporelles durant l’Épiclassique mésoaméricain (600 à 900 apr. j.‑c.) - Juliette Testard (Ateliers d'Anthropologie)
The Epiclassic period (600 to 900 A.D.) was a time of great upheaval on the central Mesoamerian Altiplano. The iconography of Cacaxtla-Xochitecatl (Tlaxcala) and Xochicalco (Morelos) is markedly different—especially in its representation of the human body—from images from Teotihuacan (Mexico). Whereas the body is a container or medium in Teotihuacan, in Cacaxtla-Xochitecatl and Xochicalco it seems to simultaneously turn into a material that is at once living and sacrificed, connected with a tangible and pragmatic reality. It is in contact with Mayan and Gulf societies that the elites from the two sites in question renew the representation of the human figure, in search of another performative strategy that will guarantee their political legitimization in a context of competition between regional centres.